Work stress and psychosocial risk factors - Ejaita Mitaire (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Resolution 2646 of 2008 aims to provide the parameters in the identification of psychosocial risks at work, this as a product of occupational stress, this article presents in a concise and understandable way for the employee in general, the meaning of psychosocial risk factors and the repercussions that these may have on their health. The Ministry of Protection includes pathologies derived from work stress in the table of Occupational Diseases, and for this it relies on the protocol for determining the origin of pathologies derived from stress and on the battery of instruments to assess psychosocial risk factors and contribute to the decision-making of work professionals in determining the origin of diseases derived from stress, whether of common or professional origin. In this case, companies must allocate human and economic resources for the identification, evaluation, prevention, intervention and monitoring of said psycho-occupational risks, it is the responsibility of the employer to ensure the health of its employees, breaching the provisions of the Ministry will be subject to sanctions in accordance with the provisions of subsections a and c of article 91 of Decree Law 1295 of 1994.